Use of the painDETECT questionnaire to differentiate the nature of hip pain associated with a labrum tear - Mitsufumi Nakawaki; Kensuke Fukushima; Gen Inoue; Mitsutoshi Moriya; Katsufumi Uchiyama; Naonobu Takahira; Masashi Takaso (Elsevier, 2018)
The nature of pain associated with a labrum tear of the hip joint can vary widely among patients and does not always correlate with findings from diagnostic imaging. Identifying the components of the pain (nociceptive, neuropathic, or mixed pattern) is important to direct treatment. This report aimed to describe the use of the painDETECT questionnaire as a screening tool in order to classify the nature of the pain in three patients who presented with pain that was atypical for a labrum tear. The painDETECT questionnaire was an effective tool to identify appropriate pain management strategies in each case.